2022
DOI: 10.2147/jir.s346505
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals a Link Between Hippo Signaling Pathway and Macrophages in Lungs of Mice with OVA-Induced Allergic Asthma

Abstract: Purpose The Hippo signaling pathway participates in the restriction of cell proliferation and organ growth. Activated macrophages have been implicated in the pathogenesis of allergic asthma. Recent studies have shown that Hippo signaling pathway may also be involved in the regulation of asthma. However, the link between Hippo signaling pathway and macrophages in the context of allergic asthma has not been investigated. The purpose of this study was to explore the link between Hippo signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This result was consistent with previous enrichment analyses, demonstrating that IFN-γ and Th17 cells had an essential effect on the development and progression of granulomatous tissues in sarcoidosis (30,31). Lymphoid enhancer-binding factor 1 (LEF1) is one of the Hippo signaling pathway hub genes, and it has been suggested that macrophage proliferation is related to the downregulation of the Hippo signaling pathway (32). The pathology of sarcoidosis is characterized by chronic granulomas with a core infiltration of macrophages and a peripheral infiltration of lymphocytes visually (33).…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with previous enrichment analyses, demonstrating that IFN-γ and Th17 cells had an essential effect on the development and progression of granulomatous tissues in sarcoidosis (30,31). Lymphoid enhancer-binding factor 1 (LEF1) is one of the Hippo signaling pathway hub genes, and it has been suggested that macrophage proliferation is related to the downregulation of the Hippo signaling pathway (32). The pathology of sarcoidosis is characterized by chronic granulomas with a core infiltration of macrophages and a peripheral infiltration of lymphocytes visually (33).…”
Section: Discussionsupporting
confidence: 92%
“…The 16S rDNA sequencing and metabolite data analysed during this study are included in its supplementary information files. The transcriptome data used in this study were retrieved from our previous study [23]. To minimize the misuse of experimental animals, the same batch of animals was used in both studies, and all other experiments in the two studies were independent and repeatable.…”
Section: Discussionmentioning
confidence: 99%
“…After the final challenge, as described previously, specific airway resistance was measured to determine airway responsiveness [23]. The mice were placed in the testing chamber for an adaptation period of 5 min, then they were separately exposed to aerosols of phosphate buffer saline (PBS) (baseline) and increasing doses of methacholine (MCh) (6.25, 12.5, and 25 mg/mL) for 3 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 CTGF is the key downstream target of YAP. 53 Continuous activation of YAP increases the expression of CTGF in renal tubular epithelial cells. 54 We found abnormal expression in kidney tissues of LN patients.…”
Section: Discussionmentioning
confidence: 99%